2015
DOI: 10.1002/14651858.cd002243.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids for treating sepsis

Abstract: BackgroundSepsis occurs when an infection is complicated by organ failures as defined by a sequential organ failure assessment (SOFA) score of two or higher. Sepsis may be complicated by impaired corticosteroid metabolism. Giving corticosteroids may benefit patients. The original review was published in 2004 and was updated in 2010 and again in 2015. ObjectivesTo examine the effects of corticosteroids on death at one month in patients with sepsis, and to examine whether dose and duration of corticosteroids inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
176
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 155 publications
(192 citation statements)
references
References 103 publications
5
176
2
4
Order By: Relevance
“…Sepsis and septic shock are major healthcare problems: they affect millions of people worldwide annually and are associated with mortality rates of 25-30% and high direct and indirect costs [35][36][37][38][39]. Pro-inflammatory cytokines have been demonstrated to either suppress cortisol response to ACTH or compete with intracellular glucocorticoid function, which can result in CIRCI in septic patients.…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…Sepsis and septic shock are major healthcare problems: they affect millions of people worldwide annually and are associated with mortality rates of 25-30% and high direct and indirect costs [35][36][37][38][39]. Pro-inflammatory cytokines have been demonstrated to either suppress cortisol response to ACTH or compete with intracellular glucocorticoid function, which can result in CIRCI in septic patients.…”
Section: Rationalementioning
confidence: 99%
“…Analysis of 27 RCTs (n = 3176) of patients with sepsis with and without shock revealed a 28-day mortality rate of 29.3% in patients receiving corticosteroids compared with 31.8% in those who received placebo [relative risk (RR) 0.87, 95% CI 0.76-1.0] [42]. The quality of evidence was considered low owing to inconsistency in the results and imprecision.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Both reviews, however, confirmed the improved shock reversal by using low-dose hydrocortisone. More recently, Annane et al included 33 eligible trials (n = 4268) in a new systematic review [304]. Of these 33 trials, 23 were at low risk of selection bias; 22 were at low risk of performance and detection bias; 27 were at low risk of attrition bias; and 14 were at low risk of selective reporting.…”
Section: H Corticosteroidsmentioning
confidence: 99%